Assessing Factors Affecting Teaching and Learning of Mathematics in Some Selected Senior High Schools in Kumasi Metropolis - Anayitime, Peter; Adobah, Emmanuel; Frimpong Ofobi, Ebenezer (International Journal of Scientific Research and Management (IJSRM), 2020)
The study sought to assess factors affecting teaching and learning of mathematics in some selected senior high schools (SHS) in Kumasi Metropolis of the Ashanti Region of Ghana. A descriptive survey was the research design used for the study. In all, a total of 90 respondents; made up of 10 SHS mathematics teachers and 80 SHS elective mathematics students were selected from five (5) SHS in the Metropolis.  A purposive sampling technique of the non-probability sampling procedure was used to select the respondents for the study. Data obtained were analysed using both quantitative and qualitative data analysis methods. It was revealed that lack of mathematics laboratories/practical rooms; lack/inadequate mathematics practical activities and the use of lecture method in teaching mathematics were the three (3) major factors affecting SHS students in the learning of mathematics in the selected schools. Again, it was observed that lack of TLMs; heavy workload on mathematics teachers and lack of mathematics laboratories/practical rooms were three (3) major factors affecting mathematics teachers in the teaching of mathematics. Finally, it was revealed that provision and use of appropriate TLMs in teaching mathematics; and engaging students in hands-on and minds-on oriented lessons were some of the strategies that could be used to improve SHS students’ academic performance in mathematics. It was therefore, recommended that Government of Ghana and other stakeholders in SHS education should build mathematics laboratories/practical rooms in all SHS in the country and also equip them with requisite TLMs so that students can learn mathematics in more practical-oriented manner instead theoretical approach being used in senior high schools.